Patient-reported functioning in major depressive disorder. (31st March 2016) - IsHak, Waguih William; James, David M.; Mirocha, James; Youssef, Haidy; Tobia, Gabriel; Pi, Sarah; Collison, Katherine L.; Cohen, Robert M.
Objectives: Compared with the general population, patients with major depressive disorder (MDD) report substantial deficits in their functioning that often go beyond the clinical resolution of depressive symptoms. This study examines the impact of MDD and its treatment on functioning. Methods: From the Sequenced Treatment Alternatives to Relieve Depression (STAR*D) trial, we analyzed complete data of 2280 adult outpatients with MDD at entry and exit points of each level of antidepressant treatment and again 12 months post treatment. Functioning was measured using the Work and Social Adjustment Scale (WSAS). Results: The results show that only 7% of patients with MDD reported within-normal functioning before treatment. The proportion of patients achieving within-normal functioning (WSAS) scores significantly increased after treatment. However, the majority of patients (>60%) were still in the abnormal range on functioning at exit. Although remitted patients had greater improvements compared with nonremitters, a moderate proportion of remitted patients continued to experience ongoing deficits in functioning after treatment (20–40%). Follow-up data show that the proportions of patients experiencing normal scores for functioning after 12 months significantly decreased from the end of treatment to the follow-up phase, from 60.1% to 49% ( p < 0.0001), a finding that was particularly significant in nonremitters. Limitations of this study include the reliance on self-report of functioning and the lack of information on patients who dropped out. Conclusion: This study points to the importance of functional outcomes of MDD treatment as well as the need to develop personalized interventions to improve functioning in MDD.